If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18p + -13 + 12p = 72p + -3 + -24p Reorder the terms: -13 + 18p + 12p = 72p + -3 + -24p Combine like terms: 18p + 12p = 30p -13 + 30p = 72p + -3 + -24p Reorder the terms: -13 + 30p = -3 + 72p + -24p Combine like terms: 72p + -24p = 48p -13 + 30p = -3 + 48p Solving -13 + 30p = -3 + 48p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-48p' to each side of the equation. -13 + 30p + -48p = -3 + 48p + -48p Combine like terms: 30p + -48p = -18p -13 + -18p = -3 + 48p + -48p Combine like terms: 48p + -48p = 0 -13 + -18p = -3 + 0 -13 + -18p = -3 Add '13' to each side of the equation. -13 + 13 + -18p = -3 + 13 Combine like terms: -13 + 13 = 0 0 + -18p = -3 + 13 -18p = -3 + 13 Combine like terms: -3 + 13 = 10 -18p = 10 Divide each side by '-18'. p = -0.5555555556 Simplifying p = -0.5555555556
| 6r^2+7r+5=0 | | (-3+2i)+(5-6i)= | | x+4+3x=8 | | 5x+4=x+32 | | (21+7)-16/2+3*5= | | -7x-10=46 | | 5x-7=-10x+9 | | 450=1200-3(t) | | 2(z+1)-3=z-3 | | 3.2+x=7.5 | | x^3+6x^2-5x=0 | | -9r=u | | x(3x-9)=0 | | 1x+4=-2 | | 21+7-16/2+3*5= | | 6-3x=10-5x | | x+3/8=-1/4 | | 6x+12=11-33 | | 0=16x^2-26x+7 | | 3(x+9)=48 | | -113=5x+-2(7x+25) | | 1s+-3=-6 | | (1/2)x+16=(2/3)x-4 | | 450=1200-3t | | x*2-12=44 | | 4ab-3ab^2= | | 45x=1548 | | 2x+15=5x-30 | | 7x=3y-12 | | 32x^2+16x-6=0 | | 9.4-0.7h+2.6-1.3d=5-2.0d-6.2 | | 0=(x^2)-5x+1 |